Seed storage behaviour and seed germination in African and Malagasy baobabs (Adansonia species) - (:unkn) unknown (My University, 2006)
The Adansonia (baobab) genus comprises seven species in Africa, six of which are endemic to Madagascar. Depending on the species, baobabs develop in widely varying ecosystems, including arid zones and savannahs, as well as dry and wet forests. Seeds from all species exhibited orthodox behaviour, tolerating dehydration to a moisture content of around 5%. There was no physical dormancy in the two species belonging to the Brevitubae section, A. grandidieri and A. suarezensis. Their seeds germinated without any prior scarification. The five other species, belonging to Adansonia and Longitubae section, have seeds with water-impermeable coats. In the case of A. digitata and A. za, the proportion of water-impermeable seeds was around two-thirds, whereas with A. rubrostipa, A. madagascariensis and A. perrieri, the proportion was >90%. Treatments allowing for the removal of physical dormancy needed to be markedly more severe with A. madagascariensis than with the other species. None the less, it seems impossible to link these characteristics and the interspecific differences to a strategy for adaptation by these species to their environment.
Keywords: African Research